'Post' interventions: Postcoloniality, poststructuralism and questions of 'after' in world politics. (November 2017) - Griffin, Penny
Thinking about 'after' and 'afterwards' in world politics necessitates thinking about complex, ambiguous and socially disruptive processes, practices, and methods of governance. Focused on locating the 'afterwards' in moments of world politics marked by ongoing, and consistently unsuccessful, responses to crisis, conflict, and questions of social, political, and economic legitimacy, this themed section spotlights two areas of particular concern. First, the section asks what it might mean to theorise 'after', and 'afterwards', in world politics. Second, it explores what opportunities are afforded in thinking about the relationship between 'afterwards' in terms of postcoloniality, governmentality, and the machinery of state building. Interested in diverse ways with 'thresholds', and the ambiguity of threshold environments, this section demonstrates the necessity of thinking about complex, ambiguous, and socially disruptive processes, practices, and methods of governance, including how the enduring impacts of past 'events' encroach upon the present in intimate and significant ways, influencing the lives, and life chances, of people throughout the world.